Penegakan Perda Kota Denpasar di Kawasan Prostitusi Belanjong Sanur - Anju Indah Sucita; I Ketut Sukadana; I Made Minggu Widyantara (Jurnal Konstruksi Hukum, 2020)
Social problems related to prostitution continue to develop from various cities, as well as the city of Denpasar as a metropolitan city where there is a place of prostitution in one of the Denpasar areas, namely Belanjong Sanur. With the Regional Regulation (Perda) of Denpasar City Number 1 of 2015 concerning Public Order, it is hoped that its implementation. Based on the background of the problem above, the purpose of this study is to determine the implementation of the Regional Regulation (Perda) of Denpasar City Number 1 of 2015 concerning Public Order in the Belanjong Sanur area and to analyze how the efforts made by the Denpasar City Government in eradicating prostitution in the Belanjong area Sanur. This type of research is empirical legal research using descriptive qualitative data analysis methods. The results showed that the implementation of the Denpasar City Regional Regulation (Perda) Number 1 of 2015 concerning Public Order in the Belanjong Sanur area, which was implemented by the Denpasar City Civil Service Police Unit (Satpol PP) has been carried out well. Furthermore, the efforts made by the Denpasar City Government in eradicating prostitution in the Belanjong Sanur area, in general, the efforts to overcome prostitution can be divided into two, namely efforts that are preventive in nature and actions that are repressive in nature. Preventively in the Belanjong Sanur area, namely conducting socialization and counseling. The law enforcement carried out by Satpol PP is by controlling the location of prostitution and making arrests, as is their obligation as the enforcer of Perda No.1 of 2015.